BIOLOGI DAN DEMOGRAFI TUNGAU MERAH Tetranychus spp. (Acari: Tetranychidae) PADA TANAMAN KEDELAI - Mamahit, Juliet M.E. (EUGENIA, 2011)
ABSTRACT Â  Red spider mite Tetranychus spp. are pest on several ornament and food plant. The objectives of this research were to study biology and demography Tetranychus spp. on soybean in condition laboratory. A piece of soybean leaf measures 3 cm2 at place above cotton in petridis. Above the leaf were put a pair red spider mite to watch the biology of mite.Â  The research of demography of red spider mite was done observation in one hundred egg that used to come from age class same (cohort). The observation was done every day until the egg become to adult. The result showed that the mean of fecundity of red spider mite were 54.16 egg. The total life time of female 13.28 day and sex ratio 1:1.5. The intrinsic rate of increase the population were 0.253 individual per day, the discrete daily growth rate were, 1.28 individual/day, the net reproduction rate were 25.515 individual/female/generation. The generation time were 13.567 days. The stable population of Tetranychus spp. in laboratory were 67.2% egg, 24.6 nymph and 8.2% adult. The intrinsic birth and death rate were 0.3 and 0.05 individual/female/day. Key words: Tetranychus spp., Demography, Soybean